Advances of Perovskite Solar Cells: Interface Engineering to Achieve High Photovoltage Performance - Tsutomu MIYASAKA (Electrochemistry, 2025)
Thin film solar cells using halide perovskite polycrystals as semiconductors are entering the stage of factory production after their power conversion efficiencies have rapidly improved to 27 %, reaching a level comparable to the highest efficiency of single-crystalline Si solar cells. To ensure stable high efficiency and long device life, further studies on the photovoltaic performance are focused on molecular level improvement of hetero junction interfaces for efficient charge transports. Among inverted p-i-n junction devices which are becoming a major structure in the perovskite photovoltaics, the device using SAMs (self-assembled monolayers) in place of hole transport layer has succeeded in obtaining high efficiencies equivalent to conventional n-i-p devices, Interface molecular engineering, including SAM-based modified interfaces, is essential for reducing charge recombination loss and enhancing photovoltage in power generation. This paper presents research progress on interface engineering for high voltage device performance and our recent efforts to design new structures of perovskite solar cell with SAM-modified hetero-junction interfaces.